Complementing macrocell deficits with either smallcells or Wi-Fi-willingness to choose based on the cost-capacity analysis - Razvan Popescu; Amirhossein Ghanbari; Jan Markendahl (International Telecommunications Society (ITS), 2013)
Nowadays, the increasing mobile data traffic adds extra pressure on the almost congested mobile networks. In order to meet the new demand, mobile operators have to improve their networks but as revenues are not expected to rise, they have to add extra capacity in a cost-efficient way. The solution might come from shifting the mobile data traffic towards indoor alternative networks, an approach known as mobile data offloading. Among indoor solutions two technologies stepped forward, Wi-Fi and smallcells. This paper analyses the two technologies as complementing solutions for macrocell layer in the mobile data offloading context. The main discussed questions are whether the two solutions are interchangeable and what are the risks and pitfalls when choosing one of the two technologies. In order to answer the research questions, based on a proposed real life deployment scenario, a capacity-cost calculation has been driven. Thus, a newly built office building lacking indoor mobile coverage has been considered. Based on the calculated offered capacity, the deployment costs for a comprehensive solution using either of the two technologies have been estimated. The cost of provisioning for different solutions is based on the fact that either of these solutions needs to be built from scratch and no former type of coverage exists.
Keywords: 330